Memoirs of civil service: innovations in administration - Kumath, Ranjit Singh (Jaipur Prakrit Bharati Academy, 2024)
All autobiography of a boy of rural background with no privileges of inheritance, educational background or family precedents, entered the IAS and tried to introduce innovations in administration. Civil Servants, trained professionally, owe to the society to contribute something new and innovative. We shall always face resistance to change but that has to be faced. I learnt from a talk, "Leave the place beret than you inherited". How much is not important. Important is "bring the change you want". These memoirs should help the new entrants to the Civil Service as a reminder to do something new, something better and something innovative to facilitate and simplify the lives of the people for whose service they have been selected. We owe a great deal and must return to the society what is due.
Keywords: IAS as an author; Memoirs of civil service